Differential response of IgM and IgG memory B cell populations to CD40L: insights of T cell – memory B cell interactions - Rincon-Arevalo, Hector; Stefanski, Ana-Luisa; Le, Tuan Anh; Cases, Marcos; Wiedemann, Annika; Szelinski, Franziska; Ritter, Jacob; Dang, Van Duc; Lino, Andreia C.; Dörner, Thomas; Schrezenmeier, Eva (Frontiers in Immunology, 2024)
Memory B cells (mBCs) are characterized by their long-term stability, fast reactivation, and capability to rapidly differentiate into antibody-secreting cells (ASCs). However, the role of T cells in the differentiation of mBCs, in contrast to naive B cells, remains to be delineated. We study the role of T cells in mBC responses, using CD40L stimulation and autologous T-B co-cultures. Our results showed that increased CD40L levels led to a selective increased proliferation of IgM+ mBC, which did not class-switched, resulting in higher frequencies of IgM+ ASCs and a lower frequency of IgG+ ASCs. The IgG+/IgA+ mBCs were unaffected. We further compared the transcription of immune-related genes in IgM+ and IgG+ pre-plasmablasts cultured at high (500 ng/mL) and low (50 ng/mL) CD40L levels. In response to increased CD40L levels, both populations exhibited a core response to genes related to activation (TRAF1, AKT3, CD69, and CD80). However, they differed in genes related to cytokine/chemokine/homing interactions (CCL3/4/17, LTA, NKX2-3, BCL2 and IL21R) and cell-cell interactions (HLADR, CD40, and ICOSL), which were largely confined to IgG+ cells. Our findings revealed that in co-cultures with a high T-ratio, the response was similar to that found in cultures with high CD40L levels. These results suggest that IgG+ mBCs have a greater capacity for proliferation and T cell interaction, and weaker migration capabilities, leading to a preference for an IgG response over IgM in the short term. This adaptable response could fine-tune the memory repertoire with different functions of IgG versus IgM mBCs.